1972
DOI: 10.1021/jo00979a018
|View full text |Cite
|
Sign up to set email alerts
|

Halo sugar nucleosides. III. Reactions for the chlorination and bromination of nucleoside hydroxyl groups

Abstract: The replacement of various hydroxyl functions in the sugar moiety of nucleosides by chlorine or bromine can be achieved through reaction with carbon tetrahalides and triphenylphosphine in DMF or DMAC. The reactions with primary hydroxyl groups are rapid and efficient while reactions of the secondary hydroxyl groups of 2'-deoxy nucleosides are slower. In the latter case, the chlorination reaction occurs principally with inversion of configuration while bromination proceeds mainly with retention of configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
4

Year Published

1978
1978
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(44 citation statements)
references
References 0 publications
4
36
0
4
Order By: Relevance
“…The reaction involves the production of a phosphonium salt used to activate a primary hydroxyl function towards nucleophic displacement [26][27][28][29] 1. For example, tri-n-butylphosphine, dialkyl disulfide, plus a ribonucleoside gave from 26-90% yield of the 5'-S-alkylthio-5'-deoxyribonucleoside [ 301, and triphenylphosphine, carbon tetrabromide, lithium azide, plus a ribonucleoside gave 45-92% yield of the 5'-azido-5'-deoxyribonucleosides [ 3 13.…”
Section: )mentioning
confidence: 99%
“…The reaction involves the production of a phosphonium salt used to activate a primary hydroxyl function towards nucleophic displacement [26][27][28][29] 1. For example, tri-n-butylphosphine, dialkyl disulfide, plus a ribonucleoside gave from 26-90% yield of the 5'-S-alkylthio-5'-deoxyribonucleoside [ 301, and triphenylphosphine, carbon tetrabromide, lithium azide, plus a ribonucleoside gave 45-92% yield of the 5'-azido-5'-deoxyribonucleosides [ 3 13.…”
Section: )mentioning
confidence: 99%
“…Treatment of 1a with TsCl gave the p-toluenesulfonate 2 (in 68% yield [7]), which was converted in acceptable yield (58%) with potassium thioacetate in acetone to compound 3 [8]. Using basic medium (NaOH, NaOMe, NH 3 in MeOH) for the 5'-deprotection of 3, we isolated the symmetric disulfide that was formed in high yield.…”
mentioning
confidence: 99%
“…Reese and co-workers introduced 9-(4-methoxyphenyl)-9H-xanthene-9-thiol (AXT) for inserting the thio modification preferentially in the synthesis of 2'-thioadenosine [10]. We followed his method for the synthesis of our 2'-deoxy-5'-thionucleosides 4 and 14 a ± c. Treatment of the 5'-OH group with CCl 4 and triphenylphosphine gave 6 in 73% yield [8]. The 5'-chloro-thymidine (6) reacted with 9-(4-methoxyphenyl)-9H-xanthene-9-thiol (AXT) and 1,1,3,3-tetramethylguanidine in 70 ± 95% yield to 5'-S-[9-(4-methoxyphenyl)-9H-xanthen-9-yl]-5'-thiothymidine (7) [10].…”
mentioning
confidence: 99%
“…Treatment of2',3'-anhydroadenosine (321)(352) with sodium ethyl mercaptide gave 9-[3-deoxy-3-( ethylthio )-fJ-D-xylofuranosyl J adenine (329). Direct treatment of (329) with cold thionyl chloride gave an 86 % yield of crystalline 9-[3-chloro-2,3-dideoxy-2-( ethylthio )-p-D-arabinofuranosyl J adenine (330).…”
Section: /3 Conversion Of a Sugar Hydroxyl To Halogen And Reactiomentioning
confidence: 99%
“…Baker and co-workers found that 9-(2-0-acetyl-5-0-methoxycarbonyl-3-O-p-tol uenes ulfonyl-p-D-ri bofuranosyl )adenine (343) ga ve, upon treatment with base, 2',3' -anhydroadenosine (321). This epoxide underwent an attack by ethylmercaptide ion at the 3' position to give 9-(3-deoxy-3-ethylthio-P-D-xylofuranosyl )adenine (329). (352) NH, NH, The "trans rule" predicts the formation of 1,2-trans-nucleosides from 2-0-acyl activated sugars (Section 2.1.1) via 1,2-acyloxonium ions.…”
Section: Preparation and Reactions Oj Miscellaneous Esters Of The Sugmentioning
confidence: 99%